Correction to the article “Clinical Trials in Portugal: How Can we Improve?”, Published on Acta Med Port 2021 Feb;34(2):80-83. - de Sousa, Carla (2021)
On the footer of page 80, affiliations of the authors, where it reads:“3. Departamento de Psicologia Clínica e da Saúde. Hospital da Luz. Lisboa. Portugal.”It should read:“3. Centro de Investigação da Learning Health. Hospital da Luz Learning Health. Lisboa. Portugal.”Article published with errors: https://www.actamedicaportuguesa.com/revista/index.php/amp/article/view/15155